Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4ta03202k
|View full text |Cite
|
Sign up to set email alerts
|

Polythiophenoazomethines – alternate photoactive materials for organic photovoltaics

Abstract: A solution processable all-thiophene polyazomethine used as a photoactive/donor layer in a bulk heterojunction photovoltaic device with PC60BM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…[18][19][20][21][22] As a further step in our contribution of developing donor-acceptor conjugated systems based on BDF, we report here on the synthesis and the electronic properties of extended BDF-thiophene derivatives 1a-d (Scheme 1). The electron donor ability of the thiophene units was strengthened by hexyloxy groups while electron withdrawing pentafluorophenyl, cyano and butylacetate groups were grafted on the BDF units.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] As a further step in our contribution of developing donor-acceptor conjugated systems based on BDF, we report here on the synthesis and the electronic properties of extended BDF-thiophene derivatives 1a-d (Scheme 1). The electron donor ability of the thiophene units was strengthened by hexyloxy groups while electron withdrawing pentafluorophenyl, cyano and butylacetate groups were grafted on the BDF units.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding polyazomethines without LC properties in the context of photovoltaic applications, some researchers proposed to use them as a donor in the active layer [67][68][69][70][71][72][73][74]. The first paper about PAZ for solar cells was published by Sharma et al [67].…”
Section: Photovoltaic Propertiesmentioning
confidence: 98%
“…On the other hand, polyazomethines synthesised from 2,5-bis(hexyloxy)-1,4-bis[(2,5-bis (hexyloxy)-4-formyl-phenylenevinylene]benzene and 4,4″-diaminop-terphenyl [71] or from 4,4 0 -diformyltriphenylamine and 4,4 0 -diaminooctafluorobiphenyl [72] with PCE values in the range of 0.02-0.04% were detected. Bolduc et al [73] received a PCE value for polyazomethines with two thiophene rings per unit equal to 0.07 and 0.22%, depending on the length of the aliphatic side chain. In our previous work [74], we proposed an applied 10-camphorsulfonic acid (CSA) as a dopant to not only improve the solubility of polyazomethine but also enhance the photovoltaic parameters of the constructed polymer solar cells and improve the morphology of the active layer.…”
Section: Photovoltaic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, PSB are recognized ICPs 42,43 with potential application areas ranging from LED devices, 44 organic photovoltaics (OPV), 45 and electrochromic devices (ECD) 46 to organic field effect transistors (OFET) 47 and chemosensors. 48 In a series of reported studies on chemical and electrochemical syntheses of several bis( pyrrole) Schiff bases, 49,50 investigations of their properties revealed that their electrical conductivities, 49 redox properties 51 and behaviour in electrochemical polymerization 52 are similar to those of polypyrrole.…”
Section: Introductionmentioning
confidence: 99%